Portret Franca Antona grofa Schrattenbacha (1712–1783) v Oaxaci - Vidmar, Polona (Zbornik za umetnostno zgodovino (Nova vrsta), 2021)
The article discusses a portrait of a young gentleman exhibited in the Museo de las Culturas de Oaxaca in Mexico. In the museum, the sitter is identified as a member of the House of Bourbon and the painting is attributed to Francesco Solimena (1657–1747). Based on the inscription on the portrait, the author identifies the sitter as Graz-born Franz Anton Count Schrattenbach (1712–1783), discusses the subject’s Grand Tour and his position in Naples, being a nephew of the former Viceroy of Naples, Wolfgang Hannibal Count Schrattenbach. The paper draws attention to the various strategies for attending a portrait during Grand Tour, applied by Schrattenbach and his peers and relatives Ignaz Maria II Count Attems (1714–1762) and Ernst Heinrich Count Wildenstein (1708–1768).
Keywords: 18. st.; 18th cent.; Franc Anton Schrattenbach; Francesco Solimena; Franz Anton Schrattenbach; Grand Tour; kavalirsko potovanje; Mehika; Mexico; portrait painting; portretno slikarstvo